A review on integrated thermochemical hydrogen production from water. (22nd January 2022) - Lee, Jung Eun; Shafiq, Iqrash; Hussain, Murid; Lam, Su Shiung; Rhee, Gwang Hoon; Park, Young-Kwon
Abstract: Hydrogen production from water splitting is considered one of the most environmentally friendly processes for replacing fossil fuels. Among the various technologies to produce hydrogen from water splitting, thermochemical cycles using chemical reagents have the advantage of scale up compared to other specific facilities or geological conditions required. According to thermochemical processes using chemical redox reactions, 2-, 3-, 4-step thermochemical water splitting cycles can generate hydrogen more efficiently due to reducing temperatures. Increasing the number of cycles or steps of thermochemical hydrogen production could reduce the required maximum temperature of the facility. In addition, recently developed hybrid thermochemical processes combined with electricity or solar energy have been studied on a large scale because of the reduced cost of hydrogen production. Additionally, hybrid thermochemical water splitting combined with renewable energy can result in not only reducing the cost, but also increasing hydrogen production efficiency in terms of energy. As for a green energy, hydrogen production from water splitting using sustainable and renewable energy is significant to protect biological environment and human health. Additionally, hybrid thermochemical water splitting is conducive to large scale hydrogen production. This paper reviews the multi-step and highly developed hybrid thermochemical technologies to produce hydrogen from water splitting based on recently published literature to understand current research achievements. Highlights: Thermochemical hydrogen production from water splitting is viable on a large scale. The multi-step thermochemical method can be an energy-saving process. Hybrid methods are plausible in terms of cost and efficiency. Renewable energy combined system is conducive to hydrogen production.